Elevation of Factor VIII in Acute Fatal Liver Necrosis - Meili, E. O; Straub, P. W (Thrombosis and Haemostasis, 1970)
1. During 1963–1967 we observed 9 patients with letal fulminant hepatitis and a usually massive elevation of plasma factor VIII activity in the presence of a severe depletion of all other coagulation factors.2. Patient plasma, diluted to 100% factor VIII activity was equally effective as normal plasma in correcting the haemophilia A defect in various systems.3. An artefact due to thrombin or other clotting intermediates has been excluded.4. The following observations suggest an increase of factor VIII protein and not only of factor VIII activity : No difference was found between normal and patient factor VIII in their behaviour during heating, pH alteration, adsorption, plasmin digestion, ammonium sulfate and euglobulin precipitation, and neutralization by a specific factor VIII inhibitor. In contrast, factor VIII artifically activated in vitro with thrombin, was inactivated more rapidly by heat and plasmin than untreated normal or patient factor VIII.5. The mechanism and possible causes for this factor VIII elevation are discussed. Factor VIII elevation is limited to the most severe cases and may therefore be of prognostic significance in liver dystrophy.